Dynamic volatility spillovers and investor sentiment components across freight-shipping markets - Melas, Konstantinos D.; Panayides, Photis; Tsouknidis, Dimitris (My University, 2022)
This paper investigates whether dynamic volatility spillovers across freight-shipping markets can be explained by a comprehensive set of indicators capturing shipping investors’ sentiment. Our results reveal that an increase in the ratio of second-hand over newbuilding vessel price triggers an increase of the transmission of economic information within both the dry-bulk and tanker segments, while an increase in the ratio of price-to-earnings, as well as in the ratio of vessels sold over vessels of the global fleet also trigger an increase of the economic information transmission within each of the dry-bulk and tanker vessels, respectively. These results have important implications for shipping-market players, as they reveal novel mechanisms of the transmission of economic information within the segments and across the sub-segments of freight-shipping markets.
Keywords: Volatility spillovers; Freight-shipping markets; Shipping sentiment; VAR models; Panel data